EKSISTENSI HAK ATAS MATERI PORNOGRAFI BERDASARKAN NORMA KESUSILAAN - Christianto, Hwian (Veritas et Justitia, 2015)
AbstractThe elucidation of Art. 4 Act No. 44, 2008 implicitly protects a personâs right to possess pornographic materials for his own use. This article argues that this reading opens up a number of moral problems.Â  For one thing what is the limit of legal and illegal porn, a question which cannot be separated from our understanding of what is considered indecent behaviour. In addition, the porn industry, the source of pornographic materials, is considered immoral or against religious precepts in itself.Â  The right to posses pornographic materials will be discussed from this perspective.Â Keywords:Â right to own porn material, moral norm, special/general right, adat law, human right